Propuesta de elaboración de un producto de alto valor nutritivo; Keto snack mix a partir de quinua, granos integrales y frutos andinos - Guerra Morillo, María José (2021)
Cereals over time are a product that has been consumed for years and thus being a primary element in the human food circle. Keto snack mix made from quinoa, whole grains and Andean fruits is a cereal that has the purpose of providing its consumers with a high nutritional value through a snack within their daily diet, its nutritional content widens the market segmentation as are\; children, adolescents, adults and athletes. From the perspective of obtaining health through a balanced diet, it was defined that it is essential to develop a proposal for the elaboration of a product of high nutritional value\; Keto snack mix made from quinoa, whole grains and Andean fruits in order to enhance its nutritional content. Simultaneously, the question is adopted ¿How does the elaboration of a product of high nutritional value influence\; Keto snack mix from quinoa, whole grains and Andean fruits in the assessment of their nutritional content?, with the purpose of clarifying certain variables for an ideal approach. To increase the support of theoretical bases according to the experiences of the target audience with the application of the methodology where the following methods are contemplated: inductive-deductive and synthetic analytical, which led to the use of types of research such as: interviews , surveys, observation and experimentation, with which results were obtained that strengthen the cereal in the duration of the useful life of the product, portions of ingredients for their content and ideal nutritional value, identification of the target public in addition to their flavors and textures.